Short-Time Intermittent Preexposure of Living Human Donors to Hyperoxia Improves Renal Function in Early Posttransplant Period: A Double-Blind Randomized Clinical Trial - Kamran Montazeri; Mohammadali Vakily; Azim Honarmand; Parviz Kashefi; Mohammadreza Safavi; Shahram Taheri; Bahram Rasoulian (Journal of Transplantation)
The purpose of this human study was to investigate the effect of oxygen pretreatment in living kidney donors on early renal function of transplanted kidney. Sixty living kidney donor individuals were assigned to receive either 8–10 L/min oxygen (Group I) by a non-rebreather mask with reservoir bag intermittently for one hour at four times (20, 16, 12, and 1 hours before transplantation) or air (Group II). After kidney transplantation, urine output, blood urea nitrogen (BUN), serum creatinine, need to additional diuretics (NTADs) in the first 24 hours after transplantation, delayed graft function (DGF), the creatinine clearance (CrCL) on 10th day, and duration of hospital stay from the first posttransplant day till normalization of renal function was recorded and compared in two groups. Mean CrCL in posttransplant day 10, NTAD after 24 hours of transplantation, and urine output during 6 hours after operation were significantly better in Group I compared with Group II (𝑃<.05). Also, DGF during the first week after operation and duration of hospital stay was less in Group I compared with Group II. Intermittent exposure of human living kidney donor to hyperoxic environment may improve renal function following kidney transplantation.